CONSECINŢELE ESTIMATE ALE ADERĂRII REPUBLICII MOLDOVA LA UNIUNEA EUROPEANĂ - Patraș, Mihai (CEP USM, 2008)
The present article illustrates the probable consequences of the future adherence of RM to EU, based on the analysis of the real consequences of the adherence of various European states to the Common Market (founded in 1957), which evolved into the actual European Union (EU). The article puts emphasis on at least 10 consequences of this kind, with necessary arguments, each of them being of a special importance for the ascending evolution of RM's economy and its whole population.
Keywords: aderare a Republicii Moldova la UE